(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
An innovative use of fiber-reinforced polymer (FRP) composite materials, to control the manifestation of local buckling in a flanged steel section, is proposed. In this method, the high stiffness and linear behavior of FRP materials are utilized to provide ‗‗bracing‘‘ against web or flange local buckling in a manner that strategically leverages the unique mechanical properties of each material in an efficient application domain. The experimental research reported is aimed at demonstrating the feasibility of using small quantities of FRP to provide cross-sectional stability through the bonding of FRP strips to flange elements of the cross-section, thereby increasing the critical load of the member constraining plastic flow in the cross-sectional flange elements and facilitating the manifestation of a well-formed and stable hysteretic response of the member under cyclic loading. The member becomes, in effect, an FRP stabilized steel section.